2010
DOI: 10.17221/234/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Relation between chemical indices of soil and earthworm abundance under chemical fertilization

Abstract: The study intended to establish how the dynamics of earthworms (Oligochaeta: Lumbricidae) changes in soil (abundance, biomass), under conditions of mineral fertilization with nitrogen and phosphorous in four different doses, in a 33-year experimental placement in the west of Romania, in wheat-soybean-maize-barley rotation. The soil indices taken into study were: pH, humus, total nitrogen, phosphorous and potassium. Statistical connections between the studied factors were realized using the dispersion analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
19
1
1
Order By: Relevance
“…The observed differences were not statistically significant. Iordache and Borza [26] reported a negative correlation between earthworm weight and phosphorus concentrations in soil, and a less pronounced tendency for earthworm abundance.…”
Section: Resultsmentioning
confidence: 96%
“…The observed differences were not statistically significant. Iordache and Borza [26] reported a negative correlation between earthworm weight and phosphorus concentrations in soil, and a less pronounced tendency for earthworm abundance.…”
Section: Resultsmentioning
confidence: 96%
“…Although pH did not show any significant differences among the treatments, the amount of it was lower in P. d. 63/51, where the abundance and biomass of earthworms were more comparable to the other treatments. Iordache and Borza (2010) found out a negative correlation of pH and phosphorus with earthworm number and biomass. They reported that the phosphorous content of soil exerted the greatest negative influence on earthworm biomass.…”
Section: Discussionmentioning
confidence: 93%
“…In comparison with periodic soil tillage (PST), permanent green cover (PGC) and straw-cover (SC) have several advantages, since they increase organic matter in the soil and intensify the activities of macro-and microorganisms (Kobel-Lamparski and Lamparski 2000). The positive influence on earthworm population and biomass was manifested in humus and total nitrogen (Iordache and Borza 2010). There is a strong positive correlation between the amounts of inorganic nitrogen applied and population of earthworms (Edwards and Lofty 2002), but the level of significance depends on the type of fertilizer treatment (Whalen et al 1998).…”
mentioning
confidence: 99%